Sistemática para busca de anterioridade: parceria entre biblioteca universitária e núcleo de inovação tecnológica - Andrade, Elizete de Aguiar (Universidade Federal de São Carlos, 2023)
As a result of the performance of the innovation system, scientific and technological information is fundamental for the development, protection and exploitation of technological solutions and innovative enterprises. In this context, universities can act as entrepreneurial institutions, through the initiatives of the academic community, supported by a set of organizational units such as the university library (BU) and the technological innovation centers (NIT). The hypothesis of this research is that the rapprochement between BU and NIT contributes to the construction of solutions that support the success of the institutional project of the entrepreneurial university in the brazilian context, from the search for solutions based on the sharing of resources and skills, focused on the institutionalization of preview search process. The general objective was to investigate the performance of BU as an active actor of the entrepreneurial university, including the realization of the process of seeking priority in partnership with organizational units, involved in the performance of technology -based enterprises. The action research method was used and the object of study was the Federal University of São Carlos (UFSCar). The results achieved comprise the characterization of the approximation between the organizational units involved with innovation initiatives and technology -based enterprises at UFSCar, and the construction of a system for the realization of the prior search process, involving: 1) diagnosis of the problem situation and proposed solution; 2) anterior search course; 3) template - anterior search protocol and; 4) anterior search manual. It is concluded that the approximation between the BU and NIT units can contribute to the construction of solutions that support the success of the institutional project of the entrepreneurial university in the brazilian context, seeking solutions based on the sharing of resources and skills, focused on the institutionalization of the process of process Search for priority, aiming at the protection of intellectual property developed by the academic community, using patent documents.
Systematic search for priors: partnership between university library and technological innovation center
Keywords: Informação tecnológica; Universidade empreendedora; Biblioteca universitária; Núcleo de inovação tecnológica; Inovação; Technological information; Entrepreneurial university; University library; Technological innovation center; Innovation; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::BIBLIOTECONOMIA